Data Processing Methods for Deep Level Transients Measurement - Nhat, Hoang Nam; Quoc Trieu, Pham (VNU Journal of Science: Mathematics - Physics; Vol 34 No 4DO - 10.25073/2588-1124/vnumap.4308, 2018)
The year 2019 marks 45 years in the development of Deep Level Transient Spectroscopy (DLTS) - the signal processing method for determination of overalpping deep levels in semiconductors. From its introduction in 1974 by David Lang (D.V. Lang, J. Appl. Phys . 45 , 1974, p.3023) to this date the DLTS method has undergone many changes and modifications: some were purely theoretical speculations, some were to also include new experimental arrangement and technique. This paper provides almost complete review on DLTS, focusing on the main three approaches widely used today. We also summarize the development of this method in the Faculty of Physics, VNU-Hanoi University of Sciences.